The Potential of Ports in North Sumatra to Increase Foreign Tourist Arrivals - Budi Rusdianto; Slamet Widodo (Universitas Kristen Indonesia Toraja, 2024)
Indonesia's tourism industry has experienced significant growth in recent years, particularly in the North Sumatra region, which boasts diverse cultures, stunning natural beauty. This study aims to explore the potential of North Sumatra's ports in supporting the tourism industry and increasing the flow of foreign tourists through these entry points. The research focuses on two major ports in the region, Belawan Port and Teluk Nibung Port, both managed by PT Pelabuhan Indonesia (Persero). These ports are equipped with international-standard passenger terminals and docking facilities for cruise ships and ferries, offering the potential to accommodate a large number of tourists. By analyzing the role and potential of these ports, along with their supporting facilities, this study seeks to provide insights into the factors driving the growth of North Sumatra's tourism industry and the challenges and opportunities faced by the sector in the coming years. The impact of port infrastructure development and the support and initiatives of local governments and related businesses on tourism in the region will also be examined. Furthermore, the importance of implementing sustainable tourism practices to ensure the long-term viability of North Sumatra's tourism industry will be discussed. The findings of this study are expected to foster a shared perception among businesses, port managers, and local governments in promoting North Sumatra's tourism industry to the world.